2018
DOI: 10.1029/2018gl077381
|View full text |Cite
|
Sign up to set email alerts
|

Topside Ionospheric Electron Temperature Observations of the 21 August 2017 Eclipse by DMSP Spacecraft

Abstract: During the 21 August 2017 eclipse two separate DMSP spacecraft passed through the lunar penumbra at local afternoon (F16) and near local sunset (F17) in the topside ionosphere at an altitude of ~850 km. Measurements of the in situ electron temperature by the Langmuir probe on each spacecraft showed regions where the temperature decreased on the order of 500 to 1,000 K in the shadow. The patterns of these decreases were sporadic inside the shadow but generally showed the same overall shape in both passes. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…Previous in situ measurements at high altitudes have shown that model electron temperature differ from observations albeit following the height distribution overall shape (Hairston et al, 2018). Moreover, topside eclipse measurements of ion composition, velocity, and temperature (Yau et al, 2018) and TEC using the radio occultation technique (Perry et al, 2019) are also not well reproduced by various ionospheric models.…”
Section: Resultsmentioning
confidence: 94%
“…Previous in situ measurements at high altitudes have shown that model electron temperature differ from observations albeit following the height distribution overall shape (Hairston et al, 2018). Moreover, topside eclipse measurements of ion composition, velocity, and temperature (Yau et al, 2018) and TEC using the radio occultation technique (Perry et al, 2019) are also not well reproduced by various ionospheric models.…”
Section: Resultsmentioning
confidence: 94%
“…For example, Hairston et al. (2018) reported a 500–1000K drop in T e during this eclipse in DMSP data. The F region T e in the direct, partial eclipse zone at the mid latitude Millstone Hill incoherent scatter radar experienced a similar temperature drop although with smaller magnitude (Goncharenko et al., 2018).…”
Section: Discussionmentioning
confidence: 86%
“…The large ascension of the F 2 layer (Figure 2) reaching its maximum near the first contact suggests that an additional driver uplifted the plasma and led to the early enhancement. Hairston et al (2018) reported the reduction in Te from ∼3500 K to ∼1500 K recorded by the Defense Meteorological Satellite Program spacecraft in the topside ionosphere at ∼850-km altitude over the Atlantic Ocean during the obscuration of the 2017 eclipse. They attributed the sporadic electron temperature decreases to the nonuniform EUV solar illumination of the ionosphere during the eclipse.…”
Section: Discussionmentioning
confidence: 99%